Religious and Social Activities-Based Character Building in Madrasah Aliyah Al Falah, Sirahan, Cluwak, Pati - Subaidi Subaidi (Jurnal Hikmatuna, 2019)
This study describes religious and social activities-based character education in Madrasah Aliyah Al Falah, Sirahan, Cluwak, Pati. This is a field research, which conducted directly in the field to obtain the required data and it employs a case study design, meaning that this research focuses on cases to be understood and analyzed in depth. The data were collected using interview, observation, and documentation. The data sources are the headmaster, the deputy of student affairs, teachers, madrasah committees, students, related parties and documents. The results of the study revealed that religious and social activities-based character education includes: first, ubudiyaah aspects, which are routine activities including purification or ablution, Zuhur congregational prayers, shaking hands after prayers, spiritual activities by pronouncing wirid after prayers and istighasah; second, the social aspect which is in the form of distributing zakat, teaching practices, community service, and collecting donation. Thus students have implemented a national character education program, includes: religious, discipline, social care, democratic, helpful, hard work, creative, independent, friendly / communicative, environmental care, and responsible.